Implementasi Aplikasi Sistem Keuangan Desa (SISKEUDES) di Desa Telukjambe Kecamatan Telukjambe Timur Kabupaten Karawang - Ramadhan, Kiki Rizki; Priyanti, Evi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The manifestation of public trust in the government's financial performance has become an important issue in the management of state finances. Village financial management also requires transparency and accountability. Therefore, the government launched the Village Financial System Application (SISKEUDES) as a form of implementation of Law Number 6 of 2014 concerning Villages. The Siskeudes application is an application used by the village government to report village funds, but in its application, there are still many problems. This study aims to see the implementation of the Siskeudes Application in Telukjambe Village, Telukjambe Timur District, Karawang Regency. This study uses the Edward III implementation model using a qualitative approach, and in determining the informants using purposive sampling. The results showed that the implementation of the Siskeudes application in Telukjambe Village was less effective, but the implementation of Siskeudes was under the regulations. Communication indicators show that communication between stakeholders is good, but there are problems with existing resources in supporting the implementation of the Siskudes application, due to the ineffective performance of the apparatus in operating the Siskeudes application. that the lack of competent resources to support the implementation of Siskeudes. In addition, indicators of disposition and bureaucratic structure in the implementation of Siskeudes are lacking, therefore the Telukjambe Village government needs to evaluate the implementation of the Siskeudes Application.